Wage inequality of US truck drivers - Kristen Monaco; Steffen Habermalz (Institute for the Study of Labor (IZA), 2011)
Using CPS data for the period 1979-2009, the wage dispersion of truck drivers (and subsets of the truck driving sample) is compared to the trends in wage dispersion of males economy-wide. We find that truckers' wages experienced a decrease in inequality post-deregulation, as expected given the literature on regulation's impact on the labor market. We also find that the wage dispersion for truckers is markedly different from males economy-wide, providing evidence that the wage distribution of truck drivers has been dominated by the changing structure of the occupation post-deregulation and largely immune to the factors that increased inequality for the aggregate labor market.
urn:nbn:de:101:1-201104113172
Keywords: J31; L92; 330; wage differentials; wage inequality; trucking; Verkehrsberufe; Straßengüterverkehr; Lohnstruktur; Deregulierung; USA